Application of Pelton Turbine in Pico Hydro Renewable Energy System at Sinar Negeri, Negeri Sakti Village - Ibrahim, Fauzi; Yonanda, Ahmad; Nugraha, Nurcahya (Politeknik Caltex Riau, 2023)
Some residents of Sinar Negeri Hamlet use the nearby spring as a place to raise freshwater fish. Residents have solely utilized this spring for everyday needs up until now, and it serves as the primary water source for fish ponds. Since technology would increase residents' productivity, they are excited about the chance to employ it in Sinar Negeri hamlet. Farmers also complain that there is no lighting surrounding the cultivation ponds, which makes it challenging for fish farmers to move around and perform their duties at night. Alternative small-scale power plants known as pico hydropower plants can be used in rural locations with rivers that continuously discharge water and a relatively modest waterfall to power a turbine that generates electricity. The spring has a head of 0.75 meters and a flow rate of 0,002 m3/s. Natural resource potential can be used to generate an environmentally friendly small-scale power plant using alternative energy. Through the use of turbine technology, potential energy from the water head and flow rate is converted into electrical energy produced by a generator with an approximate output of 8,79 watts.